K.H BUSTANI QADRI SEBAGAI TOKOH ULAMA TEMBILAHAN INDRAGIRI HILIR - Yara Tifany; Bedriati Ibrahim; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Name K.H. Bustani Qadri is very mashur for the people of Indragiri Hilir regency, as Ulama is a role model for the ummah. Even though he is gone, his name is still remembered for the people of Inhil. In his devotion in Indragiri Hilir has given birth to Qari and Qariah who have reached the National and International level in teaching the art of reading the Qur'an. Not only as a teacher of tajwid and the art of reading Al-Qur'an, he also actively provides Islamic studies in several places in Indragiri Hilir, beside Al-Huda Tembilahan Great Mosque as his teaching center. This research aims to know the whole biography of K.H Bustani Qadri, how his role in advancing Quran education in Tembilahan, as well as what methods are used K.H Bustani Qadri so that can give birth Qari and Qariah in National and International level. using a qualitative approach, a type of research whose findings are not obtained through statistical procedures or other forms of calculation. The type of research is field research (field research), namely research conducted with a direct jump to explore and examine the data related to the title. The respondents in this study are Students K.H. Bustani Qadri and People who petrified K.H Bustani Qadri in teaching the education of the Qur'an that still exists in Indragiri Hilir. While the data collection technique in this research is done by using two methods, namely: interview and documentation study. The results show that K.H Bustani Qadri has a big role in advancing the education of Al-Quran in Indragiri Hilir. Keywords: K.H Bustani Qadri, Ulama, Tembilahan